The Effect Of Applying Dictogloss Teaching Strategyon The Students Achievementin Writing Recount Text - Azizah, Siti (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2021)
The objective of the research was to investigate the effect of applying dictoglossteaching strategy on the students? achievement recount text. The objective of thestudy was to investigate wheter dictogloss strategy significantly effect on thestudents achievement in writing recount text. Dictogloss teaching strategy helps the students to write independently and this strategy would help the students to find their own topic and ideas about what they would write. The population was the 2015/2016 students of SMA AR-RAHMAN MEDAN which consisted of 60 students in two classes. They were divided into two groups: 30students for experimental group then 30 students for control group. The experimental group was given treatment by dictogloss teaching strategy and control group was taught by analysis control model. The instrument of the reseach was an written test. To know the students? achievement in writing there were some criteria as follows: Content, organization, vocabulary, language use and mechanics. The t-test, formula was implemented to find out the t-observed value of both groups as the basis to test hypotesis of this reseach. The result ofthis reseach showed that the t-observed value was greater than the t-table in which tobs was 2.40 and ttable 1.6. It shows that tobsttable (2.40 1.6). The hypotesis was accepted. It means that there was any significant effect ofapplying dictogloss teaching strategy on the students? achievement in writing recount text.